Firm Size and Efficient Entrepreneurial Activity: A Reformulation of the Schumpeter Hypothesis - Link, Albert N. (Journal of Political Economy, 1980)
This paper examines empirically the relationship between innovative activity, as measured by the rate of return to research-and-development expenditures, and firm size using a sample of firms from the chemicals and allied products industry (SIC 28). We find that size is a prerequisite for successful innovative activity. The estimated rate of return to research and development for the smaller firms is 30 percent, while for the larger size firms it is 78 percent. Statistical tests for structural stability were used to divide the sample into these two behavioral regimes.